Let one number be x
Let another number be y
ATQ
x + y = -12 => y = -x -12 {mark as the first equation}
xy = 20 { mark as the second equation}
Substituting value of y in second equation
x( -x - 12) = 20
-x² - 12x = 20
-x² - 12x - 20 = 0 { middle term splitting}
-x² -10x - 2x -20 = 0
-x( x + 10 ) -2 ( x +10 )
( -x - 2 ) ( x + 10 ) are the factors.
-x -2 = 0 x + 10 = 0
-x = 2 x = -10
x = -2
so we get two values of x i.e. -2 and -10
now substituting value of x in first equation ( x = -2 )
y = -x - 12 y = -x - 12
y = - ( -2 ) - 12 y = -(-10) - 12
y = 2 - 12 y = 10 - 12
y = -10 y = -2
So we get to know that if x = -2 then y = -10 And when x = -10 then y = -10.
Hope this help :)